Accuracy of bone surface size and cortical layer thickness measurements using cone beam computerized tomography. Issue 7 (2nd April 2012) - Gerlach, Nicolaas Lucius; Meijer, Gerrit Jacobus; Borstlap, Wilfred Ary; Bronkhorst, Ewald Maria; Bergé, Stefaan Jozef; Maal, Thomas Jan Jaap
Abstract Objectives The purpose of this study was to determine the accuracy of Cone Beam Computerized Tomography (CBCT) reconstructions in displaying bone surface size and cortical layer thickness. Materials and methods Two fresh frozen cadaver heads were scanned using a CBCT (i‐CAT™ 3D Imaging System; Imaging Sciences International Inc.). The mandibles were sectioned and digitalized for histological evaluation. Dimensions as measured on these sections were compared with CBCT measurements of the same region with the use of 3D image‐based planning software (Procera System NobelGuide™; Nobel Biocare). To allow optimal comparison between histological and CBCT sections, reference markers were placed into the mandibles. The Student t‐test was utilized to analyze the data. Differences with P‐values <0.05 were considered significant. Results The total height and width of the mandibular body, as measured on CBCT views, were larger compared with the histological values with a maximum difference of 0.33 mm (SD ± 0.34). Cortical thickness measurements were significantly thicker on CBCT sections (P < 0.006) with absolute differences ranging up to ±0.63 mm (SD ±0.28) and relative differences ranging up to 82.6%. Conclusion CBCT images (i‐CAT 3D Imaging System), viewed on the planning software Procera System NobelGuide, tend to overestimate the anatomical truth in assessing both bone height and width; especially cortical thicknesses are depicted thicker than in reality. When using CBCT images for presurgical assessment, one should be aware of this phenomenon of exaggeration of dimensions.